GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Intraspecific trait shift reflects earthworm response to land-use intensification in peat grasslands - Lianne C. Woudstra; Jacintha Ellers; Mariet M. Hefting; Taylor B. Craft; Matty P. Berg (Applied Soil Ecology, 2026)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Observations of Multiple Young-of-the-Year to Juvenile White Sharks (Carcharodon carcharias) within South-West Australian Waters and Its Implications for a Potential Nursery Area(s) - Craig P. O’Connell; Marc Payne; Shelley Payne; Luke J. Eller; Jon Shaw; Andrew McGregor; Andre Rerekura; Madison Stewart; Andrew Fox (Journal of Marine Science and Engineering, 2023)
The white shark (Carcharodon carcharias) is a globally distributed top predator. Due to its ecological importance, increasing knowledge through continued research can enhance management measures. One such facet of biological knowledge is the identification of shark nursery areas, as protection of these regions is critical to species survival. Presently, there are two known C. carcharias nursery areas in association with the Eastern Australian subpopulation; however, a nursery area associated with the Southern-Western Australian C. carcharias subpopulation has yet to be identified. Herein, we report opportunistic laser photogrammetry, stereo-photogrammetry, and baited remote underwater video systems (BRUVS) data that resulted in the identification of sixteen young-of-the-year (YOY)-juvenile C. carcharias from two separate regions (i.e., Salisbury Island and Daw Island) in South-West Australia. Additionally, anecdotal bycatch data associated with two YOY C. carcharias (i.e., 1.40 and 1.70 m total length) from another location within the Great Australian Bight are reported. While it is premature to conclude that these sites represent discrete or an expansive interconnected nursery area, the sightings success in this study is indicative that future research may want to consider implementing a study during a similar time period (i.e., February–March) while using a similar attractant methodology (i.e., bottom-set BRUVS baited with squid [Sepioteuthis australis]) to help elucidate the unique life-history characteristics of this C. carcharias subpopulation.

Endotoxin tolerance and low activation of TLR-4/NF-κB axis in monocytes of COVID-19 patients - Gilson P. Dorneles; Paula C. Teixeira; Alessandra Peres; Luiz Carlos Rodrigues Júnior; Simone Gonçalves da Fonseca; Marta Chagas Monteiro; Sarah Eller; Tiago F. Oliveira; Eliana M. Wendland; Pedro R. T. Romão (Journal of Molecular Medicine, 2023)

Repellency and toxicity of a CO2-derived cedarwood oil on hard tick species (Ixodidae) - Lina B. Flor-Weiler; Robert W. Behle; Fred J. Eller; Ephantus J. Muturi; Alejandro P. Rooney (Experimental and Applied Acarology, 2022)
The repellency and toxicity of a CO 2 -derived cedarwood oil (CWO) was evaluated against actively questing unfed nymphs of four species of hard ticks: Amblyomma americanum (L.), Dermacentor variabilis (Say), Ixodes scapularis Say, and Rhipicephalus sanguineus (Latreille). Using a vertical climb bioassay for repellency, nymphs of these species avoided a CWO-treated filter paper in proportional responses to treatment concentrations. At 60 min of exposure, I. scapularis nymphs were most sensitive with 50% repellency concentration (RC 50 ) of 19.8 µg cm −2 , compared with RC 50 of 30.8, 83.8 and 89.6 µg cm −2 for R. sanguineus, D. variabilis and A. americanum , respectively. Bioassays determined the lethal concentration for 50% (LC 50 ) and 90% (LC 90 ) mortality of nymphs exposed to CWO in treated vials after 24- and 48-h exposure. After 24 h exposure, the LC 50 values were 1.25, 3.45 and 1.42 µg cm −2 and LC 90 values were 2.39, 7.59 and 4.14 µg cm −2 for D. variabilis , I. scapularis and R. sanguineus , respectively, but had minimal effect on A. americanum . After 48 h exposure, the LC 50 values were 4.14, 0.78, 0.79 and 0.52 µg cm −2 , and LC 90 values were 8.06, 1.48, 1.54 and 1.22 µg cm −2 for A. americanum , D. variabilis , I. scapularis and R. sanguineus , respectively. The repellency of CWO on tick species decreased with time. The repellency and toxicity bioassays demonstrated concentration-dependent responses of tick nymphs to the oil, indicating the potential of the CO 2 -derived cedarwood oil be developed as an eco-friendly repellent and/or acaricide.

Disentangling the effects of plant species invasion and urban development on arthropod community composition - Wendy A. M. Jesse; Jasper Molleman; Oscar Franken; Mark Lammers; Matty P. Berg; Jocelyn E. Behm; Matthew R. Helmus; Jacintha Ellers (Global Change Biology, 2020)
Urban development and species invasion are two major global threats to biodiversity. These threats often co‐occur, as developed areas are more prone to species invasion. However, few empirical studies have tested if both factors affect biodiversity in similar ways. Here we study the individual and combined effects of urban development and plant invasion on the composition of arthropod communities. We assessed 36 paired invaded and non‐invaded sample plots, invaded by the plant Antigonon leptopus , with half of these pairs located in natural and the other half in developed land‐use types on the Caribbean island of St. Eustatius. We used several taxonomic and functional variables to describe community composition and diversity. Our results show that both urban development and A. leptopus invasion affected community composition, albeit in different ways. Development significantly increased species richness and exponential Shannon diversity, while invasion had no effect on these variables. However, invasion significantly increased arthropod abundance and caused biotic homogenization. Specifically, uninvaded arthropod communities were distinctly different in species composition between developed and natural sites, while they became undistinguishable after A. leptopus invasion. Moreover, functional variables were significantly affected by species invasion, but not by urban development. Invaded communities had higher community‐weighted mean body size and the feeding guild composition of invaded arthropod communities was characterized by the exceptional numbers of nectarivores, herbivores, and detritivores. With the exception of species richness and exponential Shannon diversity, invasion influenced four out of six response variables to a greater degree than urban development did. Hence, we can conclude that species invasion is not just a passenger of urban development but also a driver of change.

Heated communities: large inter- and intraspecific variation in heat tolerance across trophic levels of a soil arthropod community - Oscar Franken; Milou Huizinga; Jacintha Ellers; Matty P. Berg (Oecologia, 2018)

Global networks for invasion science: benefits, challenges and guidelines - Jasmin G. Packer; Laura A. Meyerson; David M. Richardson; Giuseppe Brundu; Warwick J. Allen; Ganesh P. Bhattarai; Hans Brix; Susan Canavan; Stefano Castiglione; Angela Cicatelli; Jan Čuda; James T. Cronin; et al. (Biological Invasions, 2017)

Radium Sampling Methods and Residence Times in St. Andrew Bay, Florida - Kirstin T. Eller; William C. Burnett; Linda M. Fitzhugh; Jeffrey P. Chanton (Estuaries and Coasts, 2014)

Traits underpinning desiccation resistance explain distribution patterns of terrestrial isopods - André T. C. Dias; Eveline J. Krab; Janine Mariën; Martin Zimmer; Johannes H. C. Cornelissen; Jacintha Ellers; David A. Wardle; Matty P. Berg (Oecologia, 2013)

Acclimation responses to temperature vary with vertical stratification: implications for vulnerability of soil‐dwelling species to extreme temperature events - Coby van Dooremalen; Matty P. Berg; Jacintha Ellers (Global Change Biology, 2013)
The occurrence of summer heat waves is predicted to increase in amplitude and frequency in the near future, but the consequences of such extreme events are largely unknown, especially for belowground organisms. Soil organisms usually exhibit strong vertical stratification, resulting in more frequent exposure to extreme temperatures for surface‐dwelling species than for soil‐dwelling species. Therefore soil‐dwelling species are expected to have poor acclimation responses to cope with temperature changes. We used five species of surface‐dwelling and four species of soil‐dwelling C ollembola that habituate different depths in the soil. We tested for differences in tolerance to extreme temperatures after acclimation to warm and cold conditions. We also tested for differences in acclimation of the underlying physiology by looking at changes in membrane lipid composition. Chill coma recovery time, heat knockdown time and fatty acid profiles were determined after 1 week of acclimation to either 5 or 20 °C. Our results showed that surface‐dwelling C ollembola better maintained increased heat tolerance across acclimation temperatures, but no such response was found for cold tolerance. Concordantly, four of the five surface‐dwelling C ollembola showed up to fourfold changes in relative abundance of fatty acids after 1 week of acclimation, whereas none of the soil‐dwelling species showed a significant adjustment in fatty acid composition. Strong physiological responses to temperature fluctuations may have become redundant in soil‐dwelling species due to the relative thermal stability of their subterranean habitat. Based on the results of the four species studied, we expect that unless soil‐dwelling species can temporarily retreat to avoid extreme temperatures, the predicted increase in heat waves under climatic change renders these soil‐dwelling species more vulnerable to extinction than species with better physiological capabilities. Being able to act under a larger thermal range is probably costly and could reduce maximum performance at the optimal temperature.

Trait plasticity in species interactions: a driving force of community dynamics - Matty P. Berg; Jacintha Ellers (Evolutionary Ecology, 2010)

Adapt or disperse: understanding species persistence in a changing world - MATTY P. BERG; E. TOBY KIERS; GERARD DRIESSEN; MARCEL Van Der HEIJDEN; BOB W. KOOI; FRANS KUENEN; MAARTJE LIEFTING; HERMAN A. VERHOEF; JACINTHA ELLERS (Global Change Biology, 2010)
The majority of studies on environmental change focus on the response of single species and neglect fundamental biotic interactions, such as mutualism, competition, predation, and parasitism, which complicate patterns of species persistence. Under global warming, disruption of community interactions can arise when species differ in their sensitivity to rising temperature, leading to mismatched phenologies and/or dispersal patterns. To study species persistence under global climate change, it is critical to consider the ecology and evolution of multispecies interactions; however, the sheer number of potential interactions makes a full study of all interactions unfeasible. One mechanistic approach to solving the problem of complicated community context to global change is to (i) define strategy groups of species based on life‐history traits, trophic position, or location in the ecosystem, (ii) identify species involved in key interactions within these groups, and (iii) determine from the interactions of these key species which traits to study in order to understand the response to global warming. We review the importance of multispecies interactions looking at two trait categories: thermal sensitivity of metabolic rate and associated life‐history traits and dispersal traits of species. A survey of published literature shows pronounced and consistent differences among trophic groups in thermal sensitivity of life‐history traits and in dispersal distances. Our approach increases the feasibility of unraveling such a large and diverse set of community interactions, with the ultimate goal of improving our understanding of community responses to global warming.